Psychological Well-Being Guru BK sebagai Professional Helper di Sekolah - Firdausi, Kristiana; Purwaningrum, Ribut (JURNAL KONSELING GUSJIGANG, 2022)
This study aimed to obtain a comprehensive depiction regarding school counselors' psychological well-being as a professional helper. The result of this study could be used as the basis for future studies to promote school counselors' psychological well-being. This study found that most respondents had not understood the concept of psychological well-being. However, they reported the majority of psychological well-being dimensions. Most of the respondents were aware of the dimensions of positive relations with others and environmental mastery. Ninety-five school counselors in this study were aware that psychological well-being is pivotal as it supports their professional performance and personal happiness. Future studies are recommended to investigate school counselors' psychological well-being further using other methods, such as case study, RnD, or mixed-method. This kind of study may indirectly improve the school counselors' understanding and competence.